A comparison of platelet count in severe preeclampsia, mild preeclampsia and normal pregnancy - Gupta, Amit; Gaur, Bindu S.; Mishra, K. B.; Dubey, Ishan (International Journal of Research in Medical Sciences, 2018)
Background: Preeclampsia, the most common of hypertensive disorders of pregnancy is an idiopathic multisystem disorder affecting 2 – 10% of all pregnancies and together they form one member of the deadly triad, along with hemorrhage and infection that contribute greatly to the maternal morbidity and mortality rates. The identification of this clinical entity and effective management play a significant role in the outcome of pregnancy. Platelet count is emphasized to play a significant role in hemostasis mechanism of preeclampsia and the degree of thrombocytopenia increases with severity of preeclampsia. This study was conducted to find correlation of platelet count in severe preeclampsia, mild preeclampsia and normal subjects. Methods: Total 140 subjects, 70 control and 70 cases were enrolled in the study. Samples for platelet count were collected and estimation was carried out by the auto-analyzers. The statistical evaluation is done using SPSS version 22 along with Anova and student t-test. Results: The mean platelet count was significantly lower (p <0.05) in mild and severe preeclampsia than that in the normal pregnancy. Decreased platelet count in severe preeclampsia was significant compared to that in mild preeclampsia. Conclusions: The frequency of thrombocytopenia was found to be directly related with the severity of disease, so platelet count can be used as a simple and cost effective tool to monitor the progression of preeclampsia, thereby preventing complications to develop during the gestational period.